2012
DOI: 10.1002/jms.2025
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the frontiers of synthetic eumelanin polymers by high‐resolution matrix‐assisted laser/desorption ionization mass spectrometry

Abstract: New trends in material science and nanotechnologies have spurred growing interest in eumelanins black insoluble biopolymers derived by tyrosinase-catalysed oxidation of tyrosine via 5,6-dihydroxyindole (DHI) and its 2-carboxylic acid (DHICA). Efficient antioxidant and photoprotective actions, associated with peculiar optoelectronic properties, are recognised as prominent functions of eumelanin macromolecules within the human and mammalian pigmentary system, making them unique candidates for the realisation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 26 publications
1
51
0
Order By: Relevance
“…X-ray diffraction studies 21,22 and scanning tunneling microscopy measurements [23][24][25] showed that the size of eumelanin protomolecules is around 15-20 Å, which suggested that the tetramers and pentamers formed by covalently bonded DHIs are the most possible molecular structures of eumelanin. Matrix-assisted laser desorption/ionization mass spectrometry studies [26][27][28][29][30][31] showed that the mass of eumelanin protomolecules is within or below B600-1,200 amu, and large polymeric structures are not observed, with the exception of the data reported in a recent report 32 . Hence, most of the investigations performed by mass spectrometry supported that the tetramers and pentamers constitute the majority of eumelanin, while slightly larger structures, such as the hexamers and octamers, are also possible.…”
mentioning
confidence: 84%
“…X-ray diffraction studies 21,22 and scanning tunneling microscopy measurements [23][24][25] showed that the size of eumelanin protomolecules is around 15-20 Å, which suggested that the tetramers and pentamers formed by covalently bonded DHIs are the most possible molecular structures of eumelanin. Matrix-assisted laser desorption/ionization mass spectrometry studies [26][27][28][29][30][31] showed that the mass of eumelanin protomolecules is within or below B600-1,200 amu, and large polymeric structures are not observed, with the exception of the data reported in a recent report 32 . Hence, most of the investigations performed by mass spectrometry supported that the tetramers and pentamers constitute the majority of eumelanin, while slightly larger structures, such as the hexamers and octamers, are also possible.…”
mentioning
confidence: 84%
“…The Raper–Mason model was first reported and has been confirmed by numerous measurements . Arzillo and Reale and co‐workers proposed that the polyamine is composed of aggregates of oligomers resulting from the polymerization of 5,6‐dihyhydroyindole (DHI) . Dreyer et al suggested that PDA is not a simple covalent polymer, but a supramolecular aggregate of monomers (mainly 5,6‐dihydroxyindoline and its dione derivative) which are assembled together through the charge transfer, and/or π‐stacking, hydrogen bonding interactions .…”
Section: Introductionmentioning
confidence: 94%
“…Recently, MALDI spectra of DHI‐melanin and N ‐methyl‐DHI‐melanin, obtained by horseradish peroxidase H 2 O 2 treatment, have been measured up to approximately 5000 and 8000 D, respectively (Reale et al., ). The findings therein are consistent with the present hypotheses and results.…”
Section: Introductionmentioning
confidence: 99%